Pemberdayaan Masyarakat Melalui Pemanfaatan Pisang Sebagai Produk Olahan Untuk Meningkatkan Pendapatan di Desa Mamben Baru Kecamatan Wanasaba Lombok Timur - Mega Safana; Rangga Alif Faresta; Raenaldi Raenaldi; Yuraeda Mufidah; Eta Lestari Kamal; Muhammad Adzy Faroby; Zamzami Zamzami; Ivo Yolanda Safitri; Novita Nurul Fakhriyah; Peny Aulia Sofy (Jurnal Pengabdian Masyarakat Sains Indonesia, 2021)
East Lombok Regency has great potential in agriculture. One of them is Mamben Baru Village, Wanasaba District in the plantation sector Banana is one of the most abundant plantation commodities, especially when the main harvest time arrives, namely from April to May. However, the problem that arises is that the people of Mamben Baru Village are not yet skilled at processing bananas into high economic value products. So that the aim of this program is to provide training in making banana-based preparations. The stages in this empowerment activity start from the preparation stage, the activity implementation stage and the product evaluation stage. The results obtained in this empowerment activity arethe creation of processed products that can help the people of Mamben Baru Village in developing processed banana products into cookies and banana chips so that they can increase community income. So that the formation of people who are skilled in processing bananas into processed products that have their own uniqueness with the flavors offered so that they have more selling power. This empowerment program provides benefits that can improve the skills of the Wanasaba Village community.